Liberalising temporary movement of natural persons : an agenda for the Development Round - Winters, L. Alan...[et al.] (2003)
Discusses the issues, difficulties and routes to further liberalising Mode 4 under the GATS, particularyly the movement of medium and low skilled service providers between developing and developed countries.